Electro-optical effects in 2D macroporous silicon structures with nanocoatings - Karachevtseva, L.A.; Lytvynenko, O.O.; Konin, K.P.; Parshyn, K.A.; Sapelnikova, O.Yuю; Stronska, O.J. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
The near-IR light absorption oscillations in 2D macroporous silicon structures with microporous silicon layers, CdTe, surface nanocrystals and SiO₂ nanocoatings have been investigated. The electro-optical effect was taken into account within the strong electric field approximation. Oscillations with a giant amplitude were observed in the spectral ranges of surface level absorption. This process is because of resonance electron scattering on the surface impurity states with the difference between two resonance energies equal to the Wannier–Stark ladder due to big scattering lifetime as compared to the electron oscillation period in the strong surface electric field. The electron transitions and free electron motion are realized due to additional change in the local electric field as a result of grazing light incidence and quasi-guided mode formation.